Some aspects of thyroid dysfunction in thalassemia major patients with severe iron overload - Cynthia Rindang; Jose R. L. Batubara; Pustika Amalia; Hindra Satari (Paediatrica Indonesiana, 2011)
Background Severe iron overload due to recurrent transfusionsÂ for chronic anemia and inadequate iron chelation therapy inÂ thalassemia major patients result in various complications,Â including hypothyroidism. Currently, there has been no data onÂ the prevalence of hypothyroidism in thalassemia major patientsÂ at the Thalassemia Centers, Department of Child Health, CiptoMangunkusumo Hospital (DCH CMH).Objective To study the prevalence of primary hypothyroidismÂ in thalassemia major patients in the Thalassemia Center, DCHÂ MCH.Methods We performed a cross-sectional, descriptive study.Â All thalassemia major subjects aged Oô€¬18 years with severe ironÂ overload underwent thyroid functionexamination. PrimaryÂ hypothyroidism was defined as either normal (compensated)Â or decreased (decompensated) free T4 (FT4) levels, along withÂ elevated sensitive thyroidô€¬stimulatinghonnone (TSH)levels.Â Results 179 subjects enrolled this study Mth male: female ratio ofÂ 1: 1.6. The prevalence of primary hypothyroidism in thalassemia majorpatients Mth severe iron overloadws26.8% (48/179). Of thoseÂ 48,45 had compensated hypothyroidism and 3 had decompensatedÂ hypothyroidism, 25.1% and 1.7% of the total subjects, respectively.Â Compensated hypothyroidism was observed in 17 subjects aged â‰¤1O years and in 28 subjects aged> 10 years. All 3 decompensatedÂ hypothyroidism cases were> 10 years of age. No relationship wasÂ found between the occurrence of primary hypothyroidism and meanÂ pre-tr811sfusion Hb levels (P=0.481, OR 1.30; 95% CI 0.63 to 2.68),Â elevated serum ferritin levels (P=0.74, OR 0.89; 95% CI 0.46 toÂ 1.75), and compliance to iron chelation therapy (P=0.570, ORÂ 0.76; 95% CI 035 to 1.65). Based on multivariate analysis, only age of <10 year-old (P=O.029, OR 0.469; 95% CI 0.23 to 0.93) wasÂ significantly associated Mth primary hypJthyroidism. Further analysisÂ using receiver operator curve (ROC) technique found that age of 8.5Â year-oldÂ was the cutoff value to predict the risk of hypothyroidism.Â Conclusion The prevalence of primary hypothyroidism in ourÂ study is high. The occurrence of hypothyroidism is associated with age.